2021
DOI: 10.3390/diagnostics11091569
|View full text |Cite
|
Sign up to set email alerts
|

Structured Reporting of Lung Cancer Staging: A Consensus Proposal

Abstract: Background: Structured reporting (SR) in radiology is becoming necessary and has recently been recognized by major scientific societies. This study aimed to build CT-based structured reports for lung cancer during the staging phase, in order to improve communication between radiologists, members of the multidisciplinary team and patients. Materials and Methods: A panel of expert radiologists, members of the Italian Society of Medical and Interventional Radiology, was established. A modified Delphi exercise was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Implementation is complex, requiring mature technology, organizational and interoperability challenges, especially adequate storage of data, and easy and adequate connections with PACS-and post-processing software. Consequently, introduction of SR should be seen as a comprehensive effort, affecting all domains of radiology [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation is complex, requiring mature technology, organizational and interoperability challenges, especially adequate storage of data, and easy and adequate connections with PACS-and post-processing software. Consequently, introduction of SR should be seen as a comprehensive effort, affecting all domains of radiology [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…According to Johns Hopkins University, case-fatality rates of COVID-19 patients ranges between 1% and 7% based on days since first confirmed case, testing efficacy, local pandemic response policies, and the population age [45][46][47][48][49]. Multi-organ manifestations of COVID-19 are now well-documented [50][51][52][53][54][55][56][57], but the potential long-term implications of these manifestations remain to be uncovered. Several studies have reported impaired exercise capacity and diffusing capacity for carbon monoxide (DL CO ) in SARS-CoV-1 survivors extending from 6 months to 15 years of follow-up [58][59][60][61][62][63][64], suggesting impairment of the intra-alveolar diffusion pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistencies with regard to content, style, and presentation can hamper information transfer and diminish the clarity of the reports, which can in turn adversely affect the extraction of the required key information by the referring physician. Therefore, FRT should be organized and re-orientated toward structured reports (SR) [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. According to the European Society of Radiology (ESR) paper on SR in radiology, the three main goals for moving from FTR to SR are quality, datafication/quantification and accessibility [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ].…”
Section: Radiologists: How We Should Reportmentioning
confidence: 99%
“…Therefore, FRT should be organized and re-orientated toward structured reports (SR) [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. According to the European Society of Radiology (ESR) paper on SR in radiology, the three main goals for moving from FTR to SR are quality, datafication/quantification and accessibility [ 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ]. With regard to quality, this is correlated to standardization.…”
Section: Radiologists: How We Should Reportmentioning
confidence: 99%
See 1 more Smart Citation